(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave energy converters (WECs) offer a promising pathway for harnessing the vast renewable energy potential of the oceans. However, achieving commercial viability and widespread deployment requires continuous improvements in their techno-economic performance. This study focuses on the optimization of the CETO WEC, a submerged buoy technology that converts wave motion into electricity, with the aim of reducing the levelized cost of energy (LCOE). Traditional optimization strategies for WECs often prioritize maximizing power output, which can lead to designs that experience high loads and forces. This, in turn, drives up the capital expenditure (CAPEX) associated with robust structural components and complex power take-off (PTO) systems, ultimately hindering economic competitiveness. This research challenges this paradigm by investigating the impact of imposing constraints on the system’s maximum loads and forces. Through a comprehensive techno-economic analysis, this study explores the trade-off between power production and structural loading in CETO WECs. Numerical models and simulations are employed to assess the performance of the device under various operating conditions and design constraints. The analysis focuses on identifying optimal configurations that minimize peak loads and stresses while maintaining acceptable levels of power output. The results demonstrate that significant reductions in maximum loads can be achieved with only a marginal decrease in power production. This finding has important implications for the design and optimization of CETO WECs. By prioritizing load reduction, it is possible to utilize lighter and less expensive materials, simplify PTO systems, and reduce maintenance requirements. These factors contribute to a lower CAPEX and ultimately a more competitive LCOE. Furthermore, this study highlights the importance of integrating economic considerations into the optimization process. While maximizing power output remains a key objective, it should be balanced against the cost implications of increased structural loads. By incorporating LCOE as a primary optimization metric, it becomes possible to identify design solutions that are both technically efficient and economically viable. This research contributes to the advancement of wave energy technology by demonstrating the potential for achieving cost reductions through load-constrained optimization. The findings provide valuable insights for WEC developers and researchers, emphasizing the need for a holistic approach that considers both technical performance and economic factors. This shift in optimization strategy can pave the way for the accelerated development and deployment of CETO and other wave energy technologies, facilitating their integration into the global renewable energy mix.